Web 2.0 Social Networks: The Role of Trust - Grabner-Kräuter, Sonja (Journal of business ethics, 2009)
Online social networks (OSNs) have gained enormous popularity in recent years. Hundreds of millions of social network users reveal great amounts of personal information in the Web 2.0 environment that is largely devoid of security standards and practices. The central question in this article is why so many social network users are being so trusting. The focus is on theory-building on trust as a critical issue in OSNs. A theoretical framework is developed, which facilitates a multi-level and multi-dimensional analysis of research problems related to trust in OSNs. First, the structural and relational underpinnings of trust in OSNs are investigated from a governance perspective that integrates concepts of social network theory, social capital and the role of value in relational exchanges. Subsequently, the focus moves to the individual’s decision to trust and to processes through which trust actually emerges. Different types and sources of trust from the trust literature and their importance for trust-related decisions and behaviours in OSNs are discussed. Several research propositions are presented, which contribute to a better understanding of the role of trust and the relevance of facets of trust and social capital in OSNs.